2016
DOI: 10.1051/0004-6361/201628288
|View full text |Cite
|
Sign up to set email alerts
|

Surface abundances of OC supergiants

Abstract: Context. Some O and B stars show unusually strong or weak lines of carbon and/or nitrogen. These objects are classified as OBN or OBC stars. It has recently been shown that nitrogen enrichment and carbon depletion are the most likely explanations for the existence of the ON class. Aims. We investigate OC stars (all being supergiants) to check that surface abundances are responsible for the observed anomalous line strengths. Methods. We perform a spectroscopic analysis of three OC supergiants using atmosphere m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…For early-B stars, the main spectral-type criterion is the relative strength of Si iv 4089 and Si iii 4552. The former line is not always quantitatively reproduced in spectroscopic analyses (Martins et al 2016), although this is not systematic, as stressed in Sect. 3 and Fig.…”
Section: Limitations Of the Present Studymentioning
confidence: 90%
“…For early-B stars, the main spectral-type criterion is the relative strength of Si iv 4089 and Si iii 4552. The former line is not always quantitatively reproduced in spectroscopic analyses (Martins et al 2016), although this is not systematic, as stressed in Sect. 3 and Fig.…”
Section: Limitations Of the Present Studymentioning
confidence: 90%
“…Slow rotation is indeed an obvious possibility to explain why the star does not show signatures of strong enough mixing that would take the N/C to higher levels. Martins et al (2016) similarly concluded that Galactic OC supergiants likely experienced very little processing through the CN or CNO cycles. They further argued that because the OC phenomenon in Galactic stars is related to the chemically unprocessed surface abundances, it is best seen in more evolved objects for which chemical processing is already strong in morphologically normal stars.…”
Section: Cno Ratiosmentioning
confidence: 96%
“…In the past decade, several studies have been published on the surface abundances of massive stars in the Galaxy (e.g. Martins et al 2015Martins et al , 2016Martins et al , 2017Mahy et al 2015;Cazorla et al 2017;Markova et al 2018;Carneiro et al 2019) or in the Magellanic Clouds (e.g. Rivero González et al 2012;Bouret et al 2013;Grin et al 2017).…”
Section: Dependence On Metallicitymentioning
confidence: 99%
“…A direct reading of the CNO abundances suggests that they would have to be be primordial in AV 69. Martins et al (2016) similarly concluded that Galactic OC supergiants likely experienced very little processing through the CN or CNO cycles. They further argued that because the OC phenomenon in Galactic stars is related to the chemically unprocessed surface abundances, it is best seen in more evolved objects for which chemical processing is already strong in morphologically normal stars.…”
Section: Cno Ratiosmentioning
confidence: 96%
“…In the past decade, several studies have been published on the surface abundances of massive stars in the Galaxy (e.g. Martins et al 2015;Mahy et al 2015;Martins et al 2016Martins et al , 2017Cazorla et al 2017;Markova et al 2018;Carneiro et al 2019) or in the Magellanic Clouds (e.g. Rivero González et al 2012;Bouret et al 2013;Grin et al 2017).…”
Section: Dependence On Metallicitymentioning
confidence: 99%